Kirlianographic investigation of the anthropogenic factors influence on biota - Kurik, M. V.; Pesotskay, L. A.; Glukhova, N. V.; Nikogosyan, L. R. (Journal of Education, Health and Sport, 2017)
Kurik M. V., Pesotskay L. A., Glukhova N. V., Nikogosyan L. R. Kirlianographic investigation of the anthropogenic factors influence on biota. Journal of Education, Health and Sport. 2017;7(1):359-368 eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.268736 http://ojs.ukw.edu.pl/index.php/johs/article/view/4237 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2017; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.01.2017. Revised 16.01.2017. Accepted: 24.01.2017. UDK 577.3 KIRLIANOGRAPHIC INVESTIGATION OF THE ANTHROPOGENIC FACTORS INFLUENCE ON BIOTA M. V. Kurik1, L. A. Pesotskay2, N. V. Glukhova3, L. R. Nikogosyan4 1Ukrainian Institute ecology of man, Kyiv; 2 SE “Dnipropetrovsk Medical Academy of health Ministry of Ukraine”, Dnipro; 3SE “National Mining University”, Dnipro; 4Odessa National Medical University, Odessa Summary The energetic interaction between biota objects using kirlianography on film was studied. The positive effect of the Shungite room, unified by green healing clay on the human energy was established. The free-radical reactions in the water spaces followed by photons release in the ultraviolet portion of the spectrum which corresponds to the Kirlian glow. The following criteria for water energy conditions evaluation were used: the width of a crown illumination, the clear tape drives presence in it; the coronal inner region characteristics (presence of blackouts, grain). Completed computer analysis based on the histogram of brightness of pixels used methodology flicker noise spectroscopy. According to it the identified natural water as well as the water from the holy sources parameters were compared with the same in distilled water. The influence of thinking on human bioenergy, water and minerals was established. Key words: Kirlian photography, anthropogenic factors, biosphere.